Termite diversity and infestation levels on Eucalyptus pellita plantations in Riau, Indonesia - SRI RAHAYU PRASTYANINGSIH; SURYO HARDIWINOTO; MUSYAFA MUSYAFA; DARYONO PREHATEN; IRWAN EFFENDY; NURFATURAHMAN RIDWAN; FITRI KHUSYU AINI; GILANG VAZA BENATAR (Society for Indonesian Biodiversity, 2025)
Abstract. Prastyaningsih SR, Hardiwinoto S, Musyafa, Prehaten D, Effendy I, Ridwan N, Aini FK, Benatar GV. 2025. Termite diversity and infestation levels on Eucalyptus pellita plantations in Riau, Indonesia. Biodiversitas 26: 5495-5504. Eucalyptus pellita is used in industrial plantations due to its high productivity. However, monoculture plantations are vulnerable to termite infestations, which can reduce wood volume. This study aimed to assess termite infestation in E. pellita plantations in Riau, Indonesia. A total of 5,791 trees were surveyed across 24 plots representing different stand ages to determine the incidence and intensity of termite damage. Specimens from infested trees were identified morphologically and molecularly using the mitochondrial cytochrome oxidase subunit II COII gene marker and phylogenetic analysis was applied to confirm species-level identification. Three termite species were identified: Coptotermes sepangensis, Nasutitermes matangensis, and Microcerotermes havilandi. Infestation was recorded in 3-4-year-old stands, with 5th rotation plots exhibiting greater severity than 4th rotation plots; among all species, Microcerotermes caused the greatest damage, followed by Nasutitermes and Coptotermes. Across all stands, 301 trees (5.2%) were found to be infested. Damage severity was assessed by observing trunk conditions, especially when termite mounds covered half or the entire diameter, and volume loss was estimated using Huber’s formula. The highest infestation intensity (21.5%) occurred in the 4th rotation, although most cases were classified as mild (scale 1). In contrast, the 5th rotation showed higher infestation severity, with 12.3% of trees severely damaged (scale 4), resulting in the greatest wood volume loss. In 5th rotation, three-year-old tree showed the highest loss of volume, estimated at 9.10%, or 7.54 m³/ha. This is the first molecular confirmation (COII) report of termite infestation on E. pellita in Riau. The results provide baseline information on species composition, infestation patterns and associated wood loss in E. pellita plantations.